The Influence Of Hole Radius On The Properties Of Photonic Crystal Fiber - Huda Masood Mohamad; Abdulghafoor Ibrahim Abdullah (College of Education for Pure Sciences, 2008)
Abstract The influence of air hole radius on the numerical aperture, total dispersion, effective area, and nonlinear coefficient for the photonic crystal fibers are investigated. This study shows, when the pitch size and the number of rings holes are held constant, the increasing of air hole radius up to 0.8m gives better coupling efficiency due to the increasing in numerical aperture. The results show that the zero dispersion point is shifted toward the shorter wavelength due to the increasing of air hole radius. The PCF structure of 0.8 m gives an effective area 10 µm2, nonlinear coefficient 16 km-1W-1 and zero dispersion at communication wavelength 1.0m. While the same structure gives negative dispersion 80 ps/(nm.km), effective area 8 m2 and nonlinear coefficient 19.8 km-1W-1 at communication wavelength 0.8 m of Ti-Za laser.